The Relationship Between Maternal Nutrition Knowledge and Energy Intake in Lunchbox and Children's Nutritional Status - Elfanny Elfanny; Hardi Fatma Tresno Ingtyas; Nila Reswari Haryana; Yatty Destani Sandy (Universitas Negeri Semarang, 2025)
Nutritional status describes fulfilling nutritional needs through the intake and use of nutrients. Nutritional status is influenced by maternal nutritional knowledge, energy intake, and the status of working mothers. This study aims to determine the relationship between maternal nutrition knowledge and energy intake in lunchboxes and the nutritional status of children in the kindergarten of the Pengharapan Sejati Indonesia foundation. The design of this study is cross-sectional; the sample uses a total sampling technique of 46 respondents. This research was carried out in September 2024 - January 2025 at the Yayasan Pengharapan Sejati Indonesia. The data analysis was descriptive, Spearman's rank, and logistic regression. The results showed that the nutritional knowledge of the medium category of mothers was 23 respondents (50%). Energy intake for 25 children (54.3%) was in the low category. The nutritional status of malnourished children was 25 children (54.3%). The rank-spearman test results on the maternal nutrition knowledge variable were obtained with a p-value of 0.000. The variable energy intake in the lunchbox obtained a p-value of 0.002. The results of the logistical regression analysis of the nutritional knowledge variable with the nutritional status of the child obtained a p-value of 0.002 with an Exp B of 1.102, which means that every 1 point increase in nutritional knowledge provides a 1.102 times greater chance of a normal child nutritional status. The variable of energy intake in lunchboxes with nutritional status was obtained with a p-value of 0.264, meaning there was no relationship between the variable of energy intake in lunchboxes and nutritional status. This study concludes that there was a relationship between maternal nutrition knowledge and child nutritional status, and there was no relationship between energy intake in lunchboxes and children's nutritional status.